2014
DOI: 10.3899/jrheum.131284
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Treatment with Endothelin Receptor Antagonist Bosentan and Iloprost Improves Fingertip Blood Perfusion in Systemic Sclerosis

Abstract: Longterm treatment of SSc patients with ET-1 antagonism, in combination with ILO, seems to increase fingertip blood perfusion, as well as both capillary dilation capacity and number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 18 publications
3
54
0
1
Order By: Relevance
“…The tendency of ΔFBP to increase in the ILO + BOSE group and to decrease in the ILO group confirms the influence exerted by the ERA treatment on microvasculature reactivity as also previously reported 6,16,26 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The tendency of ΔFBP to increase in the ILO + BOSE group and to decrease in the ILO group confirms the influence exerted by the ERA treatment on microvasculature reactivity as also previously reported 6,16,26 .…”
Section: Discussionsupporting
confidence: 72%
“…Previous longterm followup studies showed that treatment with BOSE in combination with ILO interferes with the progression of nailfold microvascular damage, but evaluated through less-sensitive methods such as semiquantitative scoring of capillary number by NVC and fingertip blood perfusion (FBP) by LDF 15,16 .…”
Section: Rheumatologymentioning
confidence: 99%
“…9 In 2014, the longterm treatment of patients with SSc who had digital ulcers with ERA plus a vasodilator (iloprost) prevented the progression of microvascular damage as assessed by nailfold videocapillaroscopy and by analysis of peripheral blood flow. 10 This therapeutic approach is also included in the new recommendations. 1 More recent techniques to evaluate local skin blood per fusion, such as laser speckle contrast analysis (LASCA, a noncontact and safe tool already validated in SSc), offer the possibility to evaluate digital ulcer progression during combined treatment with standard systemic therapies and local medications.…”
Section: Sscmentioning
confidence: 98%
“…Several clinical studies suggested that both iloprost and bosentan are able to positively affect the scleroderma [30][31][32]. In 2012 Guiducci et al observed in nine patients with SSc complicated by arterial pulmonary hypertension a change of scleroderma pattern from ''late'' to ''active'' in seven patients after 12 months of treatment with bosentan, while NVC pattern remained unchanged in nine SSc patients treated with iloprost.…”
Section: Discussionmentioning
confidence: 95%